Analisis Faktor Employee Engagement terhadap Kinerja Karyawan di PT Sinkona Indonesia Lestari - Christina Amanda Savitri; Ni Luh Putu Nia Anggraeni; Dony Firman Santosa (Jurnal Manajemen dan Organisasi, 2023)
Length of work is one of the assessments or determinants that can show that the company has engaged employees. PT Sinkona Indonesia Lestari (PT SIL) has employees who have worked for more than 16 years as much as 62,25 percent, this shows that many employees at PT SIL feel engaged with the company. Based on this background, this research was conducted at PT SIL which aimed to find out and analyze what factors influence employee engagement on performance or employee performance at PT SIL. The sample for this study includes 100 of his employees with a stratified random sample. The variables used to describe employee engagement factors are leadership, compensation, and organizational culture. Other potential variables are employee engagement and employee performance. Organizational culture (organizational culture) has been shown to have a significant positive impact on both employee engagement and employee performance (employee performance).